EFEK STRATEGI CUSTOMER RELATIONSHIP MARKETING TERHADAP LOYALITAS PELANGGAN KLINIK GERASIA SUMBAWA BESAR - Amelia, Leli Rizki; Rahayu, Sri; Asmini, A (Fakultas Ekonomi dan Manajemen, 2023)
This research aims to examine the effect of customer relationship marketing strategies on customer loyalty at the Gerasia Clinic in Sumbawa Besar. This research uses an associative design which aims to measure the influence of the customer relationship marketing variable (X) on customer loyalty at the Gerasia Clinic in Sumbawa Besar variable (Y). The data used is quantitative data in the form of respondents' answers obtained directly using a questionnaire. The respondents in this research were 96 customers at the Gerasia Clinic in Sumbawa Besar and were selected using non-probability sampling in the form of accidental sampling. Data that has been collected using a questionnaire is processed using the SPSS application and then analyzed using simple linear regression analysis techniques, partial hypothesis testing (t test), and coefficient of determination test (R2). Based on the data analysis that has been carried out, the results obtained show that the customer relationship marketing strategy has a positive and significant effect on customer loyalty at the Gerasia Clinic in Sumbawa Besar. The ability of the customer relationship marketing variable to influence changes in customer loyalty variables at the Gerasia Clinic in Sumbawa Besar is 12.6% and is in the weak category, while the remaining 87.4% is influenced by other variables outside this research model, such as price, promotion and product and service quality.